Individual changes in neuromuscular performance in the Spanish women’s national football team throughout the 2023 World Cup - Romero-Moraleda, Blanca; Mazola, Ismel; Vasquez-Bonilla, Aldo A; González-García, Jaime (Biology of Sport, 2025)
The aim of this study was to track the neuromuscular performance of the Spanish national women’s football team during the 2023 World Cup. Twenty elite women’s football players were assessed four times during the preparatory and competitive periods. Mean and individual changes in countermovement jump (CMJ) metrics and estimated one-repetition maximum (1RM) for back squat (BS) and hip thrust (HT) exercises were tracked. External and differential internal loads were calculated for field sessions. Strength training load was also monitored using the formula: sets×repetitions×weight×RPE . One-way ANOVA, effect sizes, and individual response analysis were applied. Significant increases in jump height ( p = 0.007; ES = 0.12 to 0.44) and concentric propulsive impulse ( p = 0.003; ES = 0.15 to 0.47) were observed in MC9 compared to the start of the training camp (MC1). The estimated 1RM in BS was greater in MC9 compared to MC1 ( p < 0.001; ES = 1.26 to 2.13), MC4 ( p = 0.016; ES = 0.33 to 1.48) and MC6 ( p = 0.008; ES = 1.08 to 2.44). Estimated 1RM in HT was greater in MC9 compared to MC1 ( p = 0.047; ES = 0.31 to 1.57) and MC4 ( p = 0.015; ES = 0.64 to 1.75). Individual analysis showed a positive response in 83% of players in jump height and BS, and in 66% in HT. The Spanish women’s football team showed improved neuromuscular performance throughout the competitive period for the FIFA Women’s 2023 World Cup, especially in the latest stage of the tournament. These results provide insights into the evolution of neuromuscular performance during tournament schedules and highlight the sensitivity of neuromuscular performance monitoring.